Awareness of sustainable development among students of Katowice Business University - Staszewska, Anna (Percepcja turystyki w przestrzeni i w czasie pandemii COVID-19, 2022)
Today, sustainable development is one of the most frequently mentioned issues and includes the various activities taken to reduce climate change. Before any activity, however it is necessary to have the appropriate knowledge and qualifications in order not to bring about changes in the place of stay. In view of the above, research was conducted among students of Górnośląska Wyższa Szkoła Handlowa in Katowice on knowledge and awareness of sustainable development. The main purpose was to find out what this knowledge was and what were the actual activities taken by contemporary students as part of sustainable development. The article indicates a proposal for activities by the students surveyed within the framework of sustainable development which may be undertaken by various entities operating on the tourist services market.